Enhancing the photovoltaic performance of GaAs/graphene Schottky junction solar cells by interfacial modification with self assembled alkyl thiol monolayer. Issue 36 (7th August 2018) - Wen, Lei; Gao, Fangliang; Yu, Yuefeng; Xu, Zhenzhu; Liu, Zhikun; Gao, Peng; Zhang, Shuguang; Li, Guoqiang
Abstract : We demonstrate the fabrication of highly-efficient GaAs/graphene Schottky junction solar cells by interfacial modification with a self-assembled alkyl thiol monolayer. Abstract : In this work, we demonstrate the fabrication of highly-efficient GaAs/graphene Schottky junction solar cells by modifying the interface of the device with a self-assembled alkyl thiol monolayer (SAM). This modification not only suppresses the oxidation of GaAs during the wet transfer process of graphene but also illustrates a special case of metal-insulator-semiconductor structured solar cell, according to X-ray photoelectron spectroscopy and transient photovoltage decay measurements. The power conversion efficiency (PCE) of the GaAs/graphene solar cells increased with increasing chain length of the SAMs. The PCE is improved from 7.7% to 11.1% by utilizing 1-octadecanethiol as the fundamental building unit for the self-assembled monolayer. This PCE value is a new record for GaAs/graphene solar cells without applying doping and anti-reflection coatings (ARCs). The chain length dependent efficiency improvement can be well-explained by considering the tunneling and recombination of carriers at the interface. By studying the device area dependent performance of devices with and without interfacial modification, thiol modified devices show great potential for large-scale fabrication of GaAs/graphene solar cells. After chemical doping and applying an ARC, the PCE of the devices can be further improved to 15.9%.